Kerugian Dampak Tidak Adanya Hubungan Ekstradisi Antara Indonesia Dengan Timor Leste - Bonus Tarigan; Rico Palentino Kacaribu; Tamaulina Br. Sembiring (Jurnal Multidisiplin Indonesia, 2024)
The aim of analyzing or researching losses from the impact of the absence of extradition relations between Indonesia and East Leste, is to find out how extradition is regulated in Indonesian national law and international law and what the government's mechanisms and policies are trying to do regarding extradition agreements for those who commit crimes in Indonesia's interests, The phenomenon of extradition of criminals between Indonesia and the East is usually only based on good relations between the two countries without any official written reference. This research was conducted to find out the urgency of establishing the Indonesia - East Leste extradition treaty. The method used in this research is the normative legal research method, which is research that examines document studies, namely using various secondary data such as statutory regulations, court decisions, legal theory, and can be the opinions of scholars. The technique of collecting legal materials used in this research is library research. The research results show that the urgency of Indonesia-East Leste research can be seen from the process of repatriating criminals who cannot run optimally because there is no extradition agreement between Indonesia and East Leste despite the potential perpetrators fleeing to neighboring countries is quite high. Apart from that, the extradition agreement is in line with the AutDedere AutJudicare principle in an effort to uphold security and order in the international community. Then, Indonesia - East Leste has not held a meeting regarding the formation of an extradition agreement even though Indonesia has made many extradition principles. The obstacles are the absence of an international treaty, a lack of understanding of the function of the extradition treaty, as well as a political review of the two countries which is still full of threats related to foreign policy.